2021
DOI: 10.1007/s11356-021-15418-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metals on activity and community of sulfate-reducing bacterial enrichments and the discovery of a new heavy metal-resistant SRB from Santos Port sediment (São Paulo, Brazil)

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…However, carbon mineralization relies on the synergistic behavior of enzymatic cocktails, including cytochrome oxidases, metal dehydrogenases, etc., which in particular are affected by heavy metals, e.g., copper (Cu). For instance, metabolic activity, primarily sulfate reduction by SRB, decreased considerably with the increasing concentrations of heavy metals, specifically Cu ( Zampieri et al, 2022 ). Hence, the antimicrobial characteristics of the Cu garnered tremendous attention for developing the marine infrastructure.…”
Section: Antagonism Between Copper Ions and Microbial Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, carbon mineralization relies on the synergistic behavior of enzymatic cocktails, including cytochrome oxidases, metal dehydrogenases, etc., which in particular are affected by heavy metals, e.g., copper (Cu). For instance, metabolic activity, primarily sulfate reduction by SRB, decreased considerably with the increasing concentrations of heavy metals, specifically Cu ( Zampieri et al, 2022 ). Hence, the antimicrobial characteristics of the Cu garnered tremendous attention for developing the marine infrastructure.…”
Section: Antagonism Between Copper Ions and Microbial Colonizationmentioning
confidence: 99%
“…Several studies have demonstrated the toxic nature of Cu toward the SRB ( Zampieri et al, 2022 ). Copper metal completely inhibits SRB mixed culture at a concentration ~ 4 mg/L ( Hao et al, 1994 ), and ~50% reduction in total cell protein was reported at a concentration of 15 μM of Cu(II) for Oleidesulfovibrio alaskensis G20 ( Tripathi et al, 2022 ).…”
Section: Antagonism Between Copper Ions and Microbial Colonizationmentioning
confidence: 99%